2020
DOI: 10.1111/jcmm.15794
|View full text |Cite
|
Sign up to set email alerts
|

miR‐5188 augments glioma growth, migration and invasion through an SP1‐modulated FOXO1‐PI3K/AKT‐c‐JUN‐positive feedback circuit

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The transcription factor NFKB1 could regulate the expression of SH3YL1, and TFAP2A could regulate the expressions of PTMA and JUN. Consistent with the results here, it was shown that SP1 could enhance JUN expression ( Yi et al, 2020 ). Since other regulatory mechanisms have not been reported, in-depth experiments should be conducted to verify the regulatory mechanisms of the mentioned genes.…”
Section: Discussionsupporting
confidence: 92%
“…The transcription factor NFKB1 could regulate the expression of SH3YL1, and TFAP2A could regulate the expressions of PTMA and JUN. Consistent with the results here, it was shown that SP1 could enhance JUN expression ( Yi et al, 2020 ). Since other regulatory mechanisms have not been reported, in-depth experiments should be conducted to verify the regulatory mechanisms of the mentioned genes.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the knockdown of FOXO1 was slightly able to increase response to the above-mentioned treatments, representing that for attaining higher levels of response, both FOXO1 and FOXO3a should be inhibited together. This gets more confusing when a recent study revealed that targeting FOXO1 by miR-5188 is necessary for the activation of PI3K/AKT/c-JUN signaling pathway in U87 and U251 glioma cell lines, supporting the tumor-suppressive side of FOXO1 [ 138 ]. Similarly, another study has shown that the anti-tumor features of herbal medicine named Xihuang Pill are exerted through dephosphorylation of Akt and mTOR, resulting in decreased phosphorylation of FOXO1 and its subsequent translocation to the nucleus to induce apoptosis [ 139 ].…”
Section: Foxo Familymentioning
confidence: 99%
“…As seen in Table 3 , most of these regulators are ncRNAs, and in their results, FOXO1 was proposed as a tumor suppressor, except in a study by Shi et al [ 149 ] which showed the opposite result. It is noteworthy to mention that some ncRNAs form a positive feedback loop that constantly represses FOXO1 expression, leading to glioma progression [ 138 , 150 , 151 ] (Fig. 5 A).…”
Section: Foxo Familymentioning
confidence: 99%